Efforts to Maintain Health by Implementing Six Step Handwashing for Middle School Students - Mulyo Wiharto; Sumartono Sumartono; Jerry Maratis (Jurnal Penelitian Pendidikan IPA, 2023)
Efforts to maintain health can be carried out with a clean and healthy lifestyle, including by washing hands 6 steps. Hands are the medium that transmits disease the most, so they must always be clean by washing hands in the 6 steps. The six steps to washing your hands start with pouring soap into your palms, rubbing your palms together, rubbing the back or back of your hands, rubbing between your fingers, rinsing off the soap and drying your hands. The results of observations in the classroom action research on 21 respondents consisting of junior high school students in Bekasi concluded that the majority of respondents (66.67%) had carried out the 6 steps of hand washing correctly. The results of observations of step-by-step hand washing stated that most respondents (72.79%) did the 6-step hand washing properly, in fact all respondents (100%) had carried out step 1 or step 1, namely pouring soap on their palms before washing. Hand. The quality of the implementation of the 6-step hand washing which was mostly good was made possible by the information obtained in the counseling conducted before the respondents carried out the practice of hand washing. The quality of the implementation of the 6-step hand washing which was mostly good was also made possible by the condition of the respondents who were mostly or 85.71% were women